The curve is "y^2=(x+1)(x-1)^2"
"(x+1)(x-1)^2\\geq 0 \\Rightarrow (x+1)\\geq 0 \\Rightarrow x\\geq -1 ."
"y=\\pm \\sqrt{(x+1)(x-1)^2}"
The graph of the curve is symmetric about the x-axis.
Graph of function "y= \\sqrt{(x+1)(x-1)^2}" :
"y(-1)= 0, y(-1)= 0."
"y'(x)= \\frac{3x^2+2x-1}{ \\sqrt{(x+1)(x-1)^2}}"
"y'(-1\/3)= 0 ;"
"y'(1)" - not exist.
The function increases for x in the interval "[-1;-\\frac{1}{3}] and [1;\\infty], (y'>0)"
The function decreasing for x in the interval "[-\\frac{1}{3};1], (y'<0)"
Let us try to find where a function is increasing or decreasing
Graph of the curve :
Comments
Leave a comment